Improved Molecular Ordering in a Ternary Blend Enables All‐Polymer Solar Cells over 18% Efficiency. Issue 8 (20th December 2022) - Cai, Yunhao; Xie, Cong; Li, Qian; Liu, Chunhui; Gao, Jiaxin; Jee, Min Hun; Qiao, Jiawei; Li, Yun; Song, Jiali; Hao, Xiaotao; Woo, Han Young; Tang, Zheng; et al.
Abstract: Although all‐polymer solar cells (all‐PSCs) show great commercialization prospects, their power conversion efficiencies (PCEs) still fall behind their small molecule acceptor‐based counterparts. In all‐polymer blends, the optimized morphology and high molecular ordering are difficult to achieve since there is troublesome competition between the crystallinity of the polymer donor and acceptor during the film‐formation process. Therefore, it is challenging to improve the performance of all‐PSCs. Herein, a ternary strategy is adopted to modulate the morphology and the molecular crystallinity of an all‐polymer blend, in which PM6:PY‐82 is selected as the host blend and PY‐DT is employed as a guest component. Benefiting from the favorable miscibility of the two acceptors and the higher regularity of PY‐DT, the ternary matrix features a well‐defined fibrillar morphology and improved molecular ordering. Consequently, the champion PM6:PY‐82:PY‐DT device produces a record‐high PCE of 18.03%, with simultaneously improved open‐circuit voltage, short‐circuit current and fill factor in comparison with the binary devices. High‐performance large‐area (1 cm 2 ) and thick‐film (300 nm) all‐PSCs are also successfully fabricated with PCEs of 16.35% and 15.70%, respectively.Moreover, 16.5 cm 2 organic solar module affords an encouraging PCE of 13.84% when using the non‐halogenated solvent, showing the great potential of "Lab‐to‐Fab" transition of all‐PSCs. Abstract : The morphology and the molecular crystallinity of an all‐polymer blend have been finely modulated by using a ternary strategy. Benefiting from the favorable miscibility of the two acceptors and the higher regularity of PY‐DT, the ternary blend features a well‐defined fibrillar morphology and improved molecular ordering, which leads to an efficiency of 18.03%, representing the highest efficiency for all‐polymer solar cells thus far.